Perilaku Petani Dalam Kegiatan Usahatani Ubi Kayu Di Desa Neglasari Kecamatan Abung Tengah Kabupaten Lampung Utara - Priantika, Adela; Rangga, Kordiyana K; Yanfika, Helvi; S, Serly Silviyanti (Fakultas Pertanian, Universitas Lampung, 2023)
The amount of cassava production is inseparable from the behavior of farmers who include knowledge, attitudes and skills in cassava farming activities, which consist of soil processing, seed preparation, planting patterns, fertilization, maintenance, until the harvest. The higher or better the behavior of farmers should be able to increase the amount of cassava production. This study aims to determine the behavior of cassava farmers in Neglasari Village, Abung Tengah District, North Lampung Regency. The research was conducted in April and May 2022. The method used is a survey method with a descriptive analysis approach. The respondents were 53 cassava farmers in Neglasari Village, Abung Tengah District, North Lampung Regency. The results showed that farmers' knowledge was included in the high category with a total percentage of 77.35 percent, farmers' attitudes were included in the high category with a total percentage of 66.05 percent, and farmer skills were included in the high category with a total percentage of 69.80 percent. Based on these three behavioral aspects, the behavior of cassava farmers in Neglasari Village, Abung Tengah District, North Lampung Regency is in the high category with a total percentage of 73.60 percent.